Branched macromonomers from catalytic chain transfer polymerisation (CCTP) as precursors for emulsion-templated porous polymers. Issue 23 (22nd May 2020) - Atkins, Christophe J.; Seow, David K.; Burns, Gerard; Town, James S.; Hand, Rachel A.; Lester, Daniel W.; Cameron, Neil R.; Haddleton, David M.; Eissa, Ahmed M.
Abstract : Catalytic chain transfer polymerisation (CCTP) is combined for the first time with emulsion-templating to generate polyHIPE materials where functionality and rigidity can be tightly tailored, broadening their scope of application. Abstract : Efforts in the synthesis of macroporous polymers have mostly been directed towards the formation of stable high internal phase emulsions (HIPEs) from commercially available monomers, limiting their scope of application. Therefore, the development of simple synthetic approaches to access tailor-made macromonomers that can be used as precursors for the formation of HIPEs, allowing the design of new generations of polyHIPE materials with bespoke chemical and physical properties, is desirable in the search for new applications. In this work, cobalt(ii ) mediated catalytic chain transfer polymerisation (CCTP) is used to polymerise ethylene glycol dimethacrylate (EGDMA), producing multi vinyl-terminated branched EGDMA polymers with tuneable branching density and degree of unsaturation. These materials are subsequently implemented as macromonomer crosslinking agents for the formulation of HIPEs. The use of acrylate comonomers as propagation promoters is found to be essential and 2-ethylhexyl acrylate (EHA), isobornyl acrylate (IBOA) and 2-methoxyethyl acrylate (MEA) are investigated as comonomers in the formulations to both facilitate the photochemical curing of the HIPEs and to impart material properties to the products. The CCTP derived branched macromonomers are fully charaterised by GPC, 1 H-NMR and MALDI–ToF spectroscopy. Scanning electron microscopy (SEM) is used to explore the morphology of the produced materials. Surface wettability experiments are conducted to evaluate the hydrophilicity of the polyHIPE surface. Compression tests are used to investigate the influence of the branching density of the CCTP macromonomers as well as the nature of comonomers on the mechanical properties of the materials.